2015
DOI: 10.1542/peds.2015-0624
|View full text |Cite
|
Sign up to set email alerts
|

Professionally Responsible Disclosure of Genomic Sequencing Results in Pediatric Practice

Abstract: Genomic sequencing is being rapidly introduced into pediatric clinical practice. The results of sequencing are distinctive for their complexity and subsequent challenges of interpretation for generalist and specialist pediatricians, parents, and patients. Pediatricians therefore need to prepare for the professionally responsible disclosure of sequencing results to parents and patients and guidance of parents and patients in the interpretation and use of these results, including managing uncertain data. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…For example, results might reveal that a parent has elevated risk for cancer or the newborn is a carrier for a recessive genetic trait, meaning that while the child is will not develop the condition, one of the parents must also a carrier and a subsequent child might be affected by the condition. 19 This information might cause parents to undergo further testing themselves, and could inform their future reproductive plans. If a child is undergoing sequencing anyway, return of carrier results to parents might, under an expanded definition of benefit, aid the family, which of course includes the child.…”
Section: Commitments To Clarity and To Benefiting Infants Family Andmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, results might reveal that a parent has elevated risk for cancer or the newborn is a carrier for a recessive genetic trait, meaning that while the child is will not develop the condition, one of the parents must also a carrier and a subsequent child might be affected by the condition. 19 This information might cause parents to undergo further testing themselves, and could inform their future reproductive plans. If a child is undergoing sequencing anyway, return of carrier results to parents might, under an expanded definition of benefit, aid the family, which of course includes the child.…”
Section: Commitments To Clarity and To Benefiting Infants Family Andmentioning
confidence: 99%
“…Research has repeatedly shown that many adults who are at familial risk for such conditions—including Huntington disease, certain breast and ovarian cancers, and Alzheimer’s—elect not to be tested for them or seek to control the timing and circumstances of the testing, 2022 decision that are foreclosed when parents agree to whole genome or whole exome sequencing or receiving results associated with adult-onset conditions. For these reasons, professional guidelines on pediatric genetic testing have long cautioned against testing children for adult onset disorders, a position that is sometimes described as maintaining the child’s “right to an open future.” 23, 24 The language of rights may be too strong, but the future interest of the infant in deciding for themselves about whether and when to learn about their risk for various adult onset conditions deserves consideration.…”
Section: Commitments To Clarity and To Benefiting Infants Family Andmentioning
confidence: 99%
“…More to the point, sequencing is beginning to transform pediatric oncology by refining the patient's cancer diagnosis and providing unexpected information about new noncancer diagnoses, risk assessment for cancer and noncancer diagnoses, reproductive risk assessment, pharmacogenomics, and variants of unknown clinical significance. [11] Incorporating into clinical practice such an as-yet unproven technology, although sophisticated and powerful, has the potential to disrupt the priorities of evidencebased practice. The result could be ethically disruptive: introducing WES will leave clinicians and parents ill prepared or unprepared to make responsible decisions about patient care based on WES results.…”
Section: Introductionmentioning
confidence: 99%
“…24 Our participants expressed no consensus on the return of variants revealing adult-onset disorders, a finding that is also aligned with previous research. 42-44 Responses in our study indicated a clear desire for clinically useful or actionable information, whether that information is needed immediately, in case of emergency, or due to an illness later in childhood. Beyond childhood, however, clinical usefulness was less apparent to the pregnant women and parents of ill children in our study, and therefore results regarding adult-onset disorders were less desirable.…”
Section: Discussionmentioning
confidence: 74%